2002
DOI: 10.1128/jcm.40.2.540-546.2002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Ehrlichia canis in Canine Carrier Blood and in Individual Experimentally Infected Ticks with a p30 -Based PCR Assay

Abstract: Detection of vector-borne pathogens is necessary for investigation of their association with vertebrate and invertebrate hosts. The ability to detect Ehrlichia spp. within individual experimentally infected ticks would be valuable for studies to evaluate the relative competence of different vector species and transmission scenarios. The purpose of this study was to develop a sensitive PCR assay based on oligonucleotide sequences from the unique Ehrlichia canis gene, p30, to facilitate studies that require moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 32 publications
1
53
0
3
Order By: Relevance
“…The E. chaffeensis 91HE17 isolate was kindly provided by Dr. David Walker at the University of Texas Medical Branch at Galveston, and the E. chaffeensis St. Vincent isolate was purchased from ATCC (Manassas, VA). DNA was isolated from infected host cells by protein digestion (0.1 mg/ml proteinase K, 10 mM Tris-HCl, pH 7.4, 1 mM EDTA, 0.45% (v/v) Tween-20, 0.45% (v/v) NP40) at 55 °C for 1 h) followed by phenol/chloroform extraction and ethanol precipitation as previously described for E. canis [13]. DNA from E. muris was provided as reported elsewhere [19].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The E. chaffeensis 91HE17 isolate was kindly provided by Dr. David Walker at the University of Texas Medical Branch at Galveston, and the E. chaffeensis St. Vincent isolate was purchased from ATCC (Manassas, VA). DNA was isolated from infected host cells by protein digestion (0.1 mg/ml proteinase K, 10 mM Tris-HCl, pH 7.4, 1 mM EDTA, 0.45% (v/v) Tween-20, 0.45% (v/v) NP40) at 55 °C for 1 h) followed by phenol/chloroform extraction and ethanol precipitation as previously described for E. canis [13]. DNA from E. muris was provided as reported elsewhere [19].…”
Section: Methodsmentioning
confidence: 99%
“…More recently, single-step reverse transcription (RT)-PCR has also been utilized to amplify an outer membrane protein-1 (omp-1) paralog, p28-10, from pools of experimentally infected ticks [12], indicating that an outer membrane protein gene sequence could provide an even more sensitive PCR assay for this organism. Indeed, an assay based on p30, which is the E. canis homolog of p28, indicated that this assay was significantly more sensitive than the respective 16S rDNA-based assay for that organism [13]. This finding could be because species-specific nucleic acid sequences, such as those often encoding outer membrane proteins, can provide greater ranges of unique targets for design of primers for PCR assays [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations